دور وكالات الترويج "EPAs" في تنمية الصادرات الوطنية "تحليل تجربة MATRADE– الوكالة الوطنية لترويج الصادرات الماليزية- وإمكانية الاستفادة منها في سورية " - أبا زيد, ثناء; قاسم, سامر; غندورة, عمر أنور (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتناول هذا البحث دور وكالات ترويج الصادرات الوطنية في تقديم الدعم للمصدرين من أجل مساعدتهم على فهم وإيجاد الأسواق لمنتجاتهم من خلال تزويدهم بسائر المعلومات المتعلقة بطبيعة الأسواق الخارجية، الفرص التجارية المتاحة، المشاركة في المعارض، تقديم فرص التدريب وغيرها من الأدوات التي تساعد على ترويج الصادرات الوطنية في الأسواق العالمية. إذ إن الاهتمام بالنشاط التصديري لا يكفي وحده فقط بل هناك أساليب لتنمية الصادرات لابد وأن تكون مرافقة لذلك النشاط حتى نضمن تحقيق التصدير لأهدافه، ومن هذه الأساليب وجود وكالات لترويج الصادرات الوطنية. وبناءً عليه جاء اختيارنا لهذه الدراسة في محاولة متواضعة لإلقاء الضوء على دور تلك الوكالات وأهدافها والمهام الموكلة إليها، بالإضافة إلى تحليل تجربة MATRADE الوكالة الوطنية لترويج الصادرات الماليزية وطبيعة عملها والخدمات التي تقدمها في سبيل الارتقاء بمستوى الصادرات الماليزية وزيادة قدرتها على مواجهة المنافسة في الأسواق الخارجية. This paper examines the role of national exports promotion agencies in exporters support to help them understanding and finding markets for their products by providing them with all information concerning the nature of foreign markets, trade opportunities, participation in exhibitions, training opportunities and other tools that help to promote national exports in global markets. Where interest in export activity alone is not enough, methods for the development of exports must be escorted by this activity in order to ensure achievement of export objectives, and one of these methods are agencies existence to promote national exports. And therefore we chose this study in a modest attempt to shed light on the role of these agencies, objectives and tasks assigned to it, as well as to analyze the experience of MATRADE national agency to promote Malaysian exports and its nature of work and services provided in order to raise the level of Malaysian exports and increase the ability of exports to face competition in foreign markets.